Urban Cartographies: Mapping Mobility and Presence. (January 2017) - Zwicker, Heather; Cooley, Heidi Rae; Verhoeff, Nanna
This special issue takes up new media in situ, addressing how new media technologies have the potential to re-orient us and, by extension, radically intervene in our understandings of place—specifically the public spaces of the city—and our place in it. We not only explore the specificities of these new media technologies and the cultural practices they afford but also highlight the intimate relationships they instantiate with their surroundings. The specific case studies highlighted in the contributors' essays discuss gaming in Canada (Engel) and Japan (Hjorth), the traces of racism in South Carolina (Cooley), the topographical footprint of settler colonialism (Zwicker et al), Hong Kong pace (Wilmott), and artistic experiments that use the city as a laboratory (Verhoeff). What holds all of these contributions together is their indebtedness to creative cartography. This special issue on Urban Cartographies explores the paradoxes of presence, co-presence and absence as represented on and generated by our living, mediating screens.